HUBUNGAN INTERTEKS LAKON BANJARAN KUNTHI KARYA PURBO ASMORO DENGAN SUMBER CERITA WAYANG - Sugeng Nugroho; Timbul Haryono; R.M. Soedarsono -; Soetarno - (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2011)
This paper aims to discover the intertextual relationship between the story Banjaran Kunthi and other basic stories which already existed beforehand, and also with a number of classical shadow puppet (wayang purwa) story sources, based on an intertextual theory in a literary study. The results of the research show that banjaran is a form of wayang story which tells about the life of a particular character in a single performance. The ideas, events, characterization, and composition of scenes which make up a banjaran story are the result of a transformation of a series of particular wayang stories, either directly or through a basic story which already existed beforehand. To a certain extent, the scenes in a banjaran story show no coherence with a number of the basic stories which are adopted and the various episodes contained in the series of wayang stories.Keywords: Banjaran Kunthi, story, intertextual relationship.